THEORETICAL FUNDAMENTALS OF PHYSICAL EDUCATION! IN THE FORMATION OF A CULTURE OF A HEALTHY LIFESTYLE FOR STUDENTS (Pedagogy of Higher and Secondary Education, 2010)
Theoretical bases of forming of culture of healthy way of life of physical education facilities are examined in the article, which functions in a cultural environment and carries cultural values for the use in everyday life of students.
Keywords: health; healthy way of life, < w'ture of healthy way of life; physa al education; theoretical knowledges from physical education; personal physical culture; values of physical culture; motive abilities and skills; athletic-hygiemcal knowledges; physical perfection